2020
DOI: 10.3389/fimmu.2020.01865
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity of Neurally Mediated Syncope and Allergic Disease in Children

Abstract: Neurally mediated syncope (NMS) is the most common underlying disease of pediatric syncope, which generally includes vasovagal syncope (VVS), postural tachycardia syndrome (POTS), and situational syncope. Allergic diseases involving the respiratory system, digestive system, skin, and other systems are prevalent in children. In recent years, increasing attention has been paid to children with the comorbidity of NMS and allergic diseases. This article reviews the featured clinical manifestations and pathogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…One of the classical mechanisms for allergy is type I hypersensitivity, which may result in mast cell degranulation and subsequent release of vasoactive substances, such as leukotrienes, histamines, and prostaglandins. 16 Furthermore, mast cell activation disorder (MCAD), a condition in which mast cells increase in number or excessively release inflammatory mediators, 31 was considered to be a comorbidity of adult POTS, and some of which might be secondary to allergic disorders. 32 , 33 A previous study on adults reported that patients with POTS were complicated with abnormal mast cell activation and significant increases in methylhistamine, leukotriene, and prostaglandin D 2 in their urine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the classical mechanisms for allergy is type I hypersensitivity, which may result in mast cell degranulation and subsequent release of vasoactive substances, such as leukotrienes, histamines, and prostaglandins. 16 Furthermore, mast cell activation disorder (MCAD), a condition in which mast cells increase in number or excessively release inflammatory mediators, 31 was considered to be a comorbidity of adult POTS, and some of which might be secondary to allergic disorders. 32 , 33 A previous study on adults reported that patients with POTS were complicated with abnormal mast cell activation and significant increases in methylhistamine, leukotriene, and prostaglandin D 2 in their urine.…”
Section: Discussionmentioning
confidence: 99%
“…5–13 A study from the United States (US) reported that the spectrum of comorbidities in children with POTS mainly included sleeping disorders, gastrointestinal dysfunction, and headache. 14 The above comorbidities may be related to the mechanisms underlying POTS, such as autonomic nervous dysfunction 15 and vascular dysfunction, 16 which may theoretically affect the clinical manifestations and prognosis of children with POTS. Investigating the impact of comorbidities on the prognosis of POTS in children would significantly deepen the understanding of the outcome of POTS and help to implement a more effective strategy in patient management.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in these children with VVS, due to the hypercatecholamine status and hypersympathetic nerve function, under the inducement factors such as sudden posture change, the Bezold-Jarisch reflex of the heart is initiated by the enhancement of compensatory myocardial contractility, which leads to the increase of vagus nerve activity and the heart rate and blood pressure continue to drop ( 10 , 11 ). This causes insufficient blood supply to the brain, resulting in chest tightness, pallor, sweating, dizziness, blurred vision, and then fainting due to inability to maintain posture ( 12 ).…”
Section: Hypercatecholamine and Hypersympathetic Nerve Function In Ch...mentioning
confidence: 99%
“…There are situational triggers such as coughing, laughing, urination, defecation, swallowing, which are common in adults [7]. However, in 90% of cases of situational syncope triggered by cough in children, with facial congestion and changes in thoracic compliance, there is a history of asthma [9].…”
Section: Clinical Presentationmentioning
confidence: 99%